Fasada kościoła „na Łazarzu” w Poznaniu. Projekt Maksymiliana Wilczewskiego - Krzyślak, Bolesława; Kurzawa, Zofia (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
The text is a minor appendix to the book The Church o f Our Lady o f Sorrows in Poznań (Poznań 2013) compiled by the two authors of the present study. The new data is a fragment of the design documentation of this church, unknown to the authors of the monographic publication at the time of writing, and discovered by Andrzej Kusztelski during his research in St. Martin’s church in Poznań. It is a design of the church’s façade signed by the builder Maksymilian Wilczewski. It is the only extinct design of this building (ultimately changed in the course of realization).